Energy restriction combined with dipeptidyl peptidase-4 inhibitor exerts neuroprotection in obese male rats - Hiranya Pintana (2018)
Copyright © 2016 The Authors. Dipeptidyl peptidase-4 (DDP-4) inhibitors and energy restriction (ER) are widely used to treat insulin resistance and type 2 diabetes mellitus. However, the effects of ER or the combination with vildagliptin on brain insulin sensitivity, brain mitochondrial function, hippocampal synaptic plasticity and cognitive function in obese insulin-resistant rats have never been investigated. We hypothesised that ER with DDP-4 inhibitor exerts better efficacy than ER alone in improving cognition in obese insulin-resistant male rats by restoring brain insulin sensitivity, brain mitochondrial function and hippocampal synaptic plasticity. A total of twenty-four male Wistar rats were divided into two groups and fed either a normal diet or a high-fat diet (HFD) for 12 weeks. At week 13, the HFD rats were divided into three subgroups (n 6/subgroup) to receive one of the following treatments: vehicle, ER (60 % of energy received during the previous 12 weeks) or ER plus vildagliptin (3 mg/kg per d, p.o.) for 4 weeks. At the end of the treatment, cognitive function, metabolic parameters, brain insulin sensitivity, hippocampal synaptic plasticity and brain mitochondrial function were determined. We found that HFD-fed rats demonstrated weight gain with peripheral insulin resistance, dyslipidaemia, oxidative stress, brain insulin resistance, impaired brain mitochondrial function and cognitive dysfunction. Although HFD-fed rats treated with ER and ER plus vildagliptin showed restored peripheral insulin sensitivity and improved lipid profiles, only ER plus vildagliptin rats had restored brain insulin sensitivity, brain mitochondrial function, hippocampal synaptic plasticity and cognitive function. These findings suggest that only a combination of ER with DPP-4 inhibitor provides neuroprotective effects in obese insulin-resistant male rats.